Evaluating the Nexus Between Foreign Ownership, Digital Transformation and Bank Performance: Evidence from Vietnam - Quang, Phung Thanh; Hang, Luong Thi Thu; Thuy, Do Thi Thu; Viet, Nguyen Anh; Anh, Tran Phuong (Indonesian Journal of Sustainability Accounting and Management, 2026)
In the context of global integration and rapid digital transformation, enhancing the long-term sustainability, resilience, and governance quality of the banking sector has become a critical priority for emerging economies such as Vietnam. This study investigates how foreign ownership and digital transformation contribute not only to bank performance but also to the broader sustainability of Vietnamese joint-stock commercial banks. Using a balanced panel dataset of 25 banks over the period 2013–2022, the study applies panel data regression with fixed effects to control for unobservable bank-specific characteristics. The empirical results indicate that foreign ownership plays a significant role in strengthening bank sustainability by improving operational efficiency. Regarding digital transformation, the findings reveal a nuanced impact of Information and Communication Technology (ICT). While the composite ICT index does not consistently show significant effects, specific ICT components—namely technical infrastructure and online banking services—emerge as key drivers of efficiency and institutional resilience. In contrast, other dimensions such as human resource infrastructure and internal ICT applications exhibit no significant contribution. These findings suggest that sustainable banking development depends not only on expanding foreign capital participation but also on prioritizing targeted digital investments that enhance operational robustness and service delivery capacity. The study provides policy implications for promoting responsible foreign ownership structures and strategic ICT development to support a more resilient, efficient, and sustainable banking system in Vietnam.